Countertransference in rape counselling - Whyle, Susan Lynn (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
The study examined rape counselling, with particular emphasis on countertransference reactions experienced by the counsellors of rape survivors. Four subjects participated in semi-focused, open-ended interviews, which were taped and transcribed verbatim. The phenomenon of countertransference was discussed, and countertransference reactions identified and examined. The management of empathic strain, in order to sustain empathic inquiry and therapeutic efficacy, was discussed. The main results of the study included the identification of common victim themes, and the feelings evoked in the counsellor in the therapeutic relationship. These included feelings of anger, hopelessness, helplessness and sadness, particularly in the counselling of children, who may be HIV positive as a result of the attack, and victims of chronic abuse. Challenges of rape counselling included shortcomings in the system, and rape myths which trivialize the crime and blame the victim. The need for education and enlightenment of both the public and magistrates on the deleterious effects of rape was emphasized by all subjects.
Keywords: Countertransference (Psychology) -- Therapeutic use; Rape victims -- Counseling of